Challenging the Patriarchy: The Jackson Family as a Model of Modern Partnership in Hidden Figures Movie - Layalia, Zahrah Zayyan (CV. Era Digital Nusantara, 2024)
This study examines the portrayal of androgyny and its contribution to a non-traditional family structure in the film Hidden Figures, focusing on the African-American couple, the Jacksons. Traditional gender roles, often reinforced by media representations, contribute to societal expectations and limitations placed on individuals within families. However, evolving societal norms challenge these traditional depictions, creating a need for exploring alternative family structures and gender expressions in media. This research addresses this gap by analyzing how the film Hidden Figures presents a nuanced depiction of an African-American family navigating gender roles in the mid-20th century. Utilizing the film theory of David Bordwell and Kristina Thompson, coupled with Betty Friedan's liberal feminist theory, this qualitative study employs descriptive analysis to uncover how androgyny manifests in the characters of Mary and Levi Jackson. The findings reveal that both characters successfully maintain their feminine and masculine characteristics in both domestic and public spheres, fostering a shared responsibility in housework, childcare, and income generation. This shared responsibility allows Mary to pursue a fulfilling career while Levi breaks free from the traditional